Atomistic understanding of extreme strain shear deformation of Copper-Graphene composites. (15th October 2022) - Gwalani, Bharat; Pole, Mayur; Whalen, Kate; Li, Shuang; Yu, Anqi; O'Callahan, Brian; Nittala, Aditya; Wang, Chongmin; Tao, Jinhui; Kappagantula, Keerti
Abstract: Copper-Graphene (Cu-Gr) composites demonstrate high strength, lubricity, and enhanced electrical and thermal conductivity compared to pure copper. A homogeneous dispersion of graphene/graphitic domains in Cu is highly desirable, which can be achieved by solid-state shear-assisted processing. A detailed understanding of structure evolution of Cu-Gr under deformation is needed. Here we subjected Gr coated Cu foils to high strain shear deformation using a tribometer to observe the distribution and reallocation of Gr in Cu matrix. A rupture and smearing of Gr layer into Cu were observed reducing the Cu grain size from 67 ± 14 μm to <10 nm, in maximum shear region close to surface. While a gradual strain accumulation further below resulted in grain rotations and dynamic recrystallization. During deformation, the Gr film was first observed to fracture into flakes and then embed into the Cu matrix. Graphitic domains observed in the Cu evinced the metastable composite microstructure with a sandwich layer of Cu2 O on the interface. The local conductance, measured by conductive atomic force microscopy, shows a fivefold increase in Cu-Gr composite region compared to pure Cu. Our study shows the feasibility of shear processing to create fine-grained Cu-Gr composites with enhanced conductivity. Graphical abstract: Image 1